DESENVOLVIMENTO DO APLICATIVO DONAR PARA MAXIMIZAR O VOLUME DE DOAÇÀ•ES DE SANGUE NO BRASIL (CIPEEX, 2022)
THIS WORK AIMS TO CREATE A MOBILE APPLICATION, AS WELL AS A WEB MANAGEMENT MODULE, AIMING TO INCREASE THE BLOOD DONATION IN BRAZIL, THROUGH AWARENESS AND DISSEMINATION OF THE RIGHTS ATTRIBUTED TO DONORS. THE GOAL OF THIS APPLICATION IS TO CONNECT A DONOR TO A DONATION SITE, SUCH AS BLOOD BANKS AND RELATED SITES, TAKING INTO ACCOUNT THE DISTANCE BETWEEN DONOR AND LOCAL. THE CONNECTION WILL BE THROUGH CAMPAIGNS THAT WILL BE DISSEMINATED THROUGH THE SOCIAL NETWORKS THROUGH THE USERS OF THE APPLICATION THROUGH INFORMATION THAT WILL BE AVAILABLE TO DONORS. THE INTENTION IS TO MAKE THESE USERS AWARE OF THE RIGHTS GRANTED TO THEM BY LAW, WHEN THEY ARE AVAILABLE TO CARRY OUT THE DONATION PROCEDURE, CONTRIBUTING TO THEIR LOYALTY AND ALLOWING A BETTER QUALITY CONTROL OF THE COLLECTED MATERIAL.THE USE OF THE APPLICATION BY THE COMMUNITY IN GENERAL IS EXPECTED TO MAXIMIZE THE INCREASE IN THE NUMBER OF BLOOD DONATIONS TO LEVELS RECOMMENDED BY THE WORLD HEALTH ORGANIZATION (WHO), AS WELL AS MAKE PEOPLE AWARE OF THE IMPORTANCE OF THIS ACT. MOREOVER, THUS, MAKE THE USE OF TECHNOLOGY AS A SOCIAL TOOL OF FUNDAMENTAL IMPORTANCE IN THE ATTEMPT TO SAVE LIVES.
Keywords: Mobile Aplication. Blood Donations.Social Webs. Social Vehicle